2003
DOI: 10.1590/s0004-282x2003000200007
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of symptomatic electrodiagnosed carpal tunnel syndrome

Abstract: -This study was done to evaluate the long-term patient's satisfaction after carpal tunnel syndrome (CTS) electrodiagnostic done between 1989 and 1994 (5 to 10 years follow-up). Mail contact was made to 528 consecutive cases with a questionnaire to be filled; 165 patients responded after 19 exclusions. CTS severity was graded from 0 (incipient) to 4 (severe) after a combination of median sensory distal latency, sensory median-radial latency difference and amplitude of the median compound muscle action potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…However, such measures can be inaccurate and may have poor inter-rater reliability [Dale et al, 2010; Smith et al, 2010], and a lack of correlation between electro-diagnostic findings and symptoms and function has been reported [Chan et al, 2007]. Further, the relationship between electro-diagnostic findings and surgical outcomes is not straight-forward [Kouyoumdjian et al, 2003; Dennerlein et al, 2002]. Second, we did not include type of surgery (endoscopic versus open) in our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…However, such measures can be inaccurate and may have poor inter-rater reliability [Dale et al, 2010; Smith et al, 2010], and a lack of correlation between electro-diagnostic findings and symptoms and function has been reported [Chan et al, 2007]. Further, the relationship between electro-diagnostic findings and surgical outcomes is not straight-forward [Kouyoumdjian et al, 2003; Dennerlein et al, 2002]. Second, we did not include type of surgery (endoscopic versus open) in our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other authors, Karsidag et al 17 have reported that the most significant electrophysiological improvement occurred after surgery, but pointed out a variable percent of cases with spontaneous improvement. Kouyoumdjian et al 9 findings added some additional difficul-ties to the understanding of CTS natural history. They concluded that, in spite of cases with short duration of symptoms had a greater improvement to conservative treatment, the majority of cases that remain symptomatic to the same conservative treatment had mild median nerve conduction abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Kouyoumdjian et al [16] received responses to a retrospective, unvalidated questionnaire from 114 open carpal tunnel release patients. The average followup time was 71 months, and the response rate was 34.8 %.…”
Section: Evidence On Open Carpal Tunnel Releasementioning
confidence: 99%